Pengaruh Disiplin Kerja dan Beban Kerja terhadap Kinerja Pegawai di Sekretariat Dewan Perwakilan Rakyat Daerah Kota Samarinda - Suzatmiko Trihardi; Yulia Tri Kusumawati; Praja Hadi Saputra (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study aims to analyze the effect of work discipline and workload on employee performance at the Samarinda City DPRD Secretariat. The background of this research is based on the importance of employee performance in supporting the smooth running of legislative tasks, and the assumption that discipline and workload are internal organizational factors that play a role in achieving this performance. The method used is quantitative with an associative approach, using multiple linear regression analysis techniques. Data were collected through distributing questionnaires to 76 respondents who are employees of the DPRD Secretariat, with saturated sampling techniques. The results showed that partially, work discipline (X1) had no significant effect on employee performance (Y), while workload (X2) had a significant effect. Simultaneously, both variables have a significant effect on performance, although the contribution of the effect is relatively low. This finding indicates that workload is a more dominant factor in influencing employee performance than work discipline. This study provides theoretical and practical implications, and recommends the need for work system evaluation and the development of more comprehensive managerial policies.